Job descriptions for financial institutions : a comprehensive reference guide - Kelly, W. Frank; Hopkins, John R. (Rolling Meadows, Illinois : Bank Administration Institute, 1987)
This guide presents a combination of job descriptions, and management guides representing several different division, department, or banking unit functions.
osc 26/09/2017
Loans
Keywords: Financial institutions--management; Banks and banking; Job descriptions